Symptomatic unruptured capillary telangiectasia of the brain stem: report of three cases and review of the literature. Issue 3 (1st September 2001) - Scaglione, C; Salvi, F; Riguzzi, P; Vergelli, M; Tassinari, C A; Mascalchi, M
Abstract : Three young patients with transient or intermittent focal neurological signs suggesting brain stem involvement are described, in whom high field MRI showed focal areas of hyperintensity in T2 weighted spin echo images, hypointensity in T2* weighted gradient echo images, and enhancement in postcontrast T1 weighted images consistent with unruptured capillary telangiectasia of the brain stem. The first patient was a 28 year old woman who complained of recurrent left ear tinnitus, exacerbated during the menstrual period; MRI demonstrated that the vascular anomaly involved the left acoustic pathway. The second patient was a 30 year old woman who had three episodes of paroxysmal left lip movement 4 weeks after child delivery; MRI showed capillary telangiectasia in the right corticonuclear pathway. The third patient, a 36 year old man, had a transient right Bell's palsy; MRI disclosed two circumscribed areas consistent with capillary telangiectasia in the left corticospinal tract and medial longitudinal fasciculus. Steroid receptors in the telangiectatic vessels walls might account for the recurrent and transient course seen in our two female patients. Awareness of the MRI features of capillary telangiectasia may help in defining the real incidence, clinical correlation, and the risk of haemorrhagic complications of these vascular malformations.